Development of S.Id. TABIR Website on Islamic Learning in Elementary School - Ani Nur Aeni; Jenuri Jenuri; Arif Hidayat; Refalina Febriani; Luthfiyah Azzahra P. H.; Wida Kurniawati (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2024)
This research is motivated by the rapid development of technology that has changed the way of learning in the 21st century and the importance of mastering technology by teachers. The purpose of this research is to develop a model of PAI learning on the S.Id TABIR website. The research method used is Design and Development (D&D) and the development design is Analyze, Design, Develop, Implement, and Evaluate (ADDIE). The study population was grade 4 students at SDN Talun, with a sample of 25 students selected through purposive sampling technique. Data was collected through interviews, tests, judge expert (expert validation, conducted by media experts and material experts). Data analysis techniques, interviews were carried out descriptively, tests were carried out using SPSS, while for expert validation with a likert scale. The results showed that this website media is feasible based on expert assessment and can be used.